2016
DOI: 10.1136/bmjopen-2015-010080
|View full text |Cite
|
Sign up to set email alerts
|

Postnuclear disaster evacuation and chronic health in adults in Fukushima, Japan: a long-term retrospective analysis

Abstract: ObjectiveJapan's 2011 Fukushima Daiichi Nuclear Power Plant incident required the evacuation of over a million people, creating a large displaced population with potentially increased vulnerability in terms of chronic health conditions. We assessed the long-term impact of evacuation on diabetes, hyperlipidaemia and hypertension.ParticipantsWe considered participants in annual public health check-ups from 2008 to 2014, administrated by Minamisoma City and Soma City, located about 10–50 km from the Fukushima nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 38 publications
4
92
2
Order By: Relevance
“…This was most likely attributable to the copayment exemption for evacuees. As the health status of the evacuees worsened after the disaster (Ebner et al 2016;Nomura et al 2016;Ohira et al 2017;Murakami et al 2017), the increases in expenditure in both short-term and long-term EOAs may also be attributable to the poor health status of the evacuees. In addition, the increases in expenditure on long-term care might be attributable to reduced availability of informal care provided by younger family members and neighbors following evacuation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was most likely attributable to the copayment exemption for evacuees. As the health status of the evacuees worsened after the disaster (Ebner et al 2016;Nomura et al 2016;Ohira et al 2017;Murakami et al 2017), the increases in expenditure in both short-term and long-term EOAs may also be attributable to the poor health status of the evacuees. In addition, the increases in expenditure on long-term care might be attributable to reduced availability of informal care provided by younger family members and neighbors following evacuation .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent research highlighted the urgent need for long-term health supports for evacuees (Fukunaga and Kumakawa 2015). Lifestyle-related diseases, such as diabetes and hyperlipidemia, emerged as major health issues in EOAs in the chronic phase after the disaster (Ebner et al 2016;Nomura et al 2016;Ohira et al 2017;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study suggested that survivors of GEJE who have experienced evacuation were more likely to develop noncommunicable diseases [8]. One consequence of the disaster was that it caused a break of social linkages, which may trigger health issues in survivors [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid life changes can lead to social isolation and psychosocial stress, which are known to be associated with poor health outcomes, including an increased risk of noncommunicable diseases. Unsurprisingly, an increase in noncommunicable disease risks, such as high blood glucose levels and hyperlipidaemia, have been found in Fukushima, 7 , 8 alongside an increased burden of psychosocial distress, a phenomenon which has been described as a physical and mental health crisis 7 . In contrast with the findings of only marginal internal radiation contamination among children and adults, 2 , 9 it appears that the increasing burden of noncommunicable diseases and mental health problems may outweigh the burden of disease caused directly by radiation.…”
mentioning
confidence: 99%